The cortical focus in childhood absence epilepsy; evidence from nonlinear analysis of scalp EEG recordings. Issue 3 (March 2018) - Sarrigiannis, Ptolemaios G.; Zhao, Yifan; He, Fei; Billings, Stephen A.; Baster, Kathleen; Rittey, Chris; Yianni, John; Zis, Panagiotis; Wei, Hualiang; Hadjivassiliou, Marios; Grünewald, Richard
Highlights: The transition into the absences is dominated by a frontocentral rise in nonlinear synchronisation. A dynamic rapidly engaging bilaterally distributed epileptic network highlights typical absences. Trails leading to the thalamus relaying homotopic areas to isochronous synchronisation during absences. Abstract: Objective: To determine the origin and dynamic characteristics of the generalised hyper-synchronous spike and wave (SW) discharges in childhood absence epilepsy (CAE). Methods: We applied nonlinear methods, the error reduction ratio (ERR) causality test and cross-frequency analysis, with a nonlinear autoregressive exogenous (NARX) model, to electroencephalograms (EEGs) from CAE, selected with stringent electro-clinical criteria (17 cases, 42 absences). We analysed the pre-ictal and ictal strength of association between homologous and heterologous EEG derivations and estimated the direction of synchronisation and corresponding time lags. Results: A frontal/fronto-central onset of the absences is detected in 13 of the 17 cases with the highest ictal strength of association between homologous frontal followed by centro-temporal and fronto-central areas. Delays consistently in excess of 4 ms occur at the very onset between these regions, swiftly followed by the emergence of "isochronous" (0–2 ms) synchronisation but dynamic time lag changes occur during SW discharges. Conclusions: In absences an initial cortico-cortical spread leads to dynamic lag changes to include periods of isochronous interhemispheric synchronisation, which we hypothesize is mediated by the thalamus. Significance: Absences from CAE show ictal epileptic network dynamics remarkably similar to those observed in WAG/Rij rats which guided the formulation of the cortical focus theory.